2014
DOI: 10.1177/0218492314548231
|View full text |Cite
|
Sign up to set email alerts
|

Experience of left atrial appendage closure performed under conscious sedation

Abstract: Percutaneous left atrial appendage occlusion can be performed safely and effectively under conscious sedation. This approach will significantly reduce the complexity and costs of this increasingly performed procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, only one case-series describing LAAO under conscious sedation has been published so far. [27] Chan et al . describe their experience in 11 subjects undergoing LAAO under sedation with fentanyl and midazolam, and report no major complications following the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only one case-series describing LAAO under conscious sedation has been published so far. [27] Chan et al . describe their experience in 11 subjects undergoing LAAO under sedation with fentanyl and midazolam, and report no major complications following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, subjects described in their study are younger, with a lower prevalence of comorbidities and better cardiac function (as reflected by the higher mean ejection fraction) as compared with those enrolled in our study. [27]…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al 31 reported on 11 patients who underwent either a WATCHMAN or an ACP device implantation. Each patient underwent the procedure under conscious sedation with intravenous midazolam and fentanyl as well as continuous TEE monitoring.…”
Section: Preoperative Evaluation For Anesthesiamentioning
confidence: 99%
“…The study showed a 100% success rate for procedure completion and no procedure-related complications from using conscious sedation. 31 Limitations of this study are that it was a small study, it was not randomized with a GETA control group to compare procedure times, and it did not address any metrics for patient satisfaction.…”
Section: Preoperative Evaluation For Anesthesiamentioning
confidence: 99%
“…The main advantage of ICE utilization is that it avoids the need for general anaesthesia or deep sedation, which can be associated with additional complications (aspiration, delirium…), lead to longer procedure-time and to additional resource utilization. Of note, a recent small study showed the feasibility of LAA closure using conscious sedation with TOE guidance [60] whereas another study described the use of an ICE-TOE probe through the oesophageal route without general anaesthesia for the monitoring of ACP device implantation [61]. ICE currently lacks multiplanar capabilities and may provide suboptimal imaging of LAA, even though the ability to move the probe in different positions may compensate these shortcomings.…”
Section: Alternative and Future Imaging Mo Dalities Intracardiac Echomentioning
confidence: 99%